Presence of the Arginine Dihydrolase Pathway in Mycoplasma - Barile, Michael F. (1966)
Barile, Michael F. (Division of Biologics Standards, National Institutes of Health, Bethesda, Md.), Robert T. Schimke, and Donald B. Riggs. Presence of the arginine dihydrolase pathway in Mycoplasma. J. Bacteriol. 91:189–192. 1966.—The presence of the arginine dihydrolase pathway was examined in 61 Mycoplasma strains representing at least 18 Mycoplasma species isolated from nine different sources: human, bovine, avian, murine, swine, goat, canine, sewage, and tissue cell culture origin. Some species were represented by only one or two strains. Different strains of the same species gave the same results. Ten species (56%) were positive. Many nonpathogenic Mycoplasma species (M. hominis, type 1 and 2, M. fermentans, M. salivarium, and M. gallinarum) were positive, whereas most pathogenic species (M. pneumoniae, M. gallisepticum, M. neurolyticum, and M. hyorhinis) were negative. The presence of arginine dihydrolase activity among Mycoplasma species may prove to be useful for purposes of identification and classification.